The influence of REM sleep and SWS on emotional memory consolidation in participants reporting depressive symptoms. (February 2018) - Harrington, Marcus O.; Johnson, Jennifer M.; Croom, Harriet E.; Pennington, Kyla; Durrant, Simon J.
Abstract: Negative emotional memory bias is thought to play a causal role in the onset and maintenance of major depressive disorder. Rapid Eye Movement (REM) sleep has been shown to selectively consolidate negative emotional memories in healthy participants, and is greater in quantity and density in depressed patients. Slow-Wave Sleep (SWS) is typically associated with the consolidation of non-emotional memories. However, the effects of REM sleep and SWS on emotional memory consolidation have not been investigated in participants reporting depressive symptoms. In this study, we recruited two groups of healthy participants; one reporting mild-to-moderate depressive symptoms, and another reporting minimal depressive symptoms (assessed using the Beck Depression Inventory; BDI-II). Using a within-subjects split-night design, we measured consolidation of positive, neutral and negative images across a 3 h retention interval rich in either REM sleep or SWS. We found a significant sleep condition x image valence interaction in participants reporting depressive symptoms [F (2, 20) = 4.73, p  = .021], but not participants reporting minimal depressive symptoms [F (2, 22) = .17, p  = .845]. Participants reporting depressive symptoms consolidated significantly more neutral memories during SWS, and marginally more negative memories during REM sleep, than those reporting minimal depressive symptoms [t (21) = 2.44, p  = .023; t (21) = 1.96, p  = .064, respectively]. Our preliminary results demonstrate that REM sleep and SWS have differential effects on the consolidation of emotional and neutral images in participants reporting depressive symptoms. Further studies including larger sample sizes are required to investigate whether REM sleep alterations promote the development of negative memory bias in major depressive disorder.